Comparison between gel and tube methods in antibody screening by using Indirect Coombs in hemoglobinopathies patients in Latakia - الشّمالي سوزان; عوّامة محمد أيمن; بدّور سراء (Latakia University Journal -Medical Sciences Series, 2022)
Antibody screening is of great importance both before blood transfusion, and in the diagnosis of hemolytic transfusion reaction (HTR) and hemolytic disease of the fetus and newborn (HDFN). Anti-human Globulin Test (AHGT), also known as Coombs Test, remains the most important test that is widely used in antibodies detection. The standard gold method for conducting this test has been the conventional tube test, but this method is not without some disadvantages, so other better methods were developed and came into use such as, solid phase tests; which include the Gel Test. This technique has spread rapidly because of its speed, ease of performance, high sensitivity and specificity as reported by several studies, although some other reports described a relative increase in some nonspecific reactions. In this study, we aim to compare the tube and gel methods in detecting antibodies formed against red blood cells alloantigens in thalassemia and sickle cell disease patients in Latakia. We conducted antibodies screening by gel and tube methods in parallel for 70 patients using IAT in Liss-coombs at 37º, and compared the results of both methods. According to our findings, the tube method remains a good option with high sensitivity and specificity.